2017
DOI: 10.1016/j.neuroscience.2017.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiac vagal tone by bradykinin acting on nucleus ambiguus

Abstract: Bradykinin (BK), a component of the kallikrein-kininogen-kinin system exerts multiple effects via B1 and B2 receptor activation. In the cardiovascular system, bradykinin has cardioprotective and vasodilator properties. We investigated the effect of BK on cardiac-projecting neurons of nucleus ambiguus, a key site for the parasympathetic cardiac regulation. BK produced a dose-dependent increase in cytosolic Ca2+ concentration. Pretreatment with HOE140, a B2 receptor antagonist, but not with R715, a B1 receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Brailoiu et al demonstrated that bradykinin acts on B2 receptors in the nuclease ambiguous to increase parasympathetic cardiac tone, ultimately leading to bradycardia 15 . Indeed, increased parasympathetic tone, as manifested by bradycardia, could be felt clinically and could mimic anaphylactoid reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Brailoiu et al demonstrated that bradykinin acts on B2 receptors in the nuclease ambiguous to increase parasympathetic cardiac tone, ultimately leading to bradycardia 15 . Indeed, increased parasympathetic tone, as manifested by bradycardia, could be felt clinically and could mimic anaphylactoid reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Its effects on cardiovascular regulation are little-known. Bradykinin modulates the parasympathetic tone acting on B 2 receptors in nucleus ambiguous [ 13 , 23 ]. However, the physiologic and pathophysiologic significance of such interaction is yet to be defined, although a role for bradykinin is suggested in some conditions such as hypertension and diabetes [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the vagus nerve has a protective role in models of inflammation such as ischemia–reperfusion injury [ 12 ]. The parasympathetic tone, acting on B 2 receptors in nucleus ambiguous, can also be modulated by bradykinin [ 13 ]. Moreover, in idiopathic systemic capillary leak syndrome, a disease characterized by unexplained episodes of plasma extravasation dealing severe hypovolemic shock, heart-rate variability (HRV) analysis showed that, during the hyperacute phase of shock, both sympathetic and vagal modulations were totally absent, mimicking the pattern of a denervated transplanted heart [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These authors advise that motor neurons of nucleus ambiguus and trigeminal afferent terminals are linked for the coordination of muscles related to swallowing phase. Similarly, trigeminal nerve and the nucleus ambiguus are involved in the heart's rhythm 28,29 . So, it is expected that swallowing influences the HRV.…”
Section: Discussionmentioning
confidence: 99%